Pyrite Biooxidation by Acidophilic Archaea AcidiplasmaSp. MBA-1 Under Varied Conditions - Bulaev, Aleksandr (KnE Life Sciences, 2022)
The goal of this research was to study pyrite (FeS2 ) bioleaching by a strain of the genus Acidiplasma under different conditions (temperature, pH) to evaluate the potential role of Acidiplasma representatives in biooxidation of this sulfide mineral. To compare the role of Acidiplasma archaea in pyrite biooxidation with other acidophilic microorganisms, the experiments were also performed with representatives of othergroups of microorganisms predominant in biohydrometallurgical processes.Pure and mixed cultures of moderately thermophilic acidophilic microorganisms, including strains Acidithiobacillus caldus MBC-1, Sulfobacillusthermosulfidooxidans VKMV 1269T and Acidiplasmasp. MBA-1, were used. The experiments were carried out in flasks with 100 mL of mineral nutrient medium supplemented with 0.02% yeast extract and 1 g of pyrite on a rotary shaker for 20 days. Bioleaching was performed at 45, 55, and 60∘С. The results demonstrated that the representatives of the genus Acidiplasmaprovided a comparatively higher rate of pyrite bioleaching at high temperatures (55 and 60∘C) and low pH of the medium (1.0). Thus, according to the results, strains of the genus Acidiplasma may provide a high rate of pyrite bioleaching at low levels ofpH. Therefore, the results suggest that archaea of the genus Acidiplasma may be promising microorganisms to improve bioleaching processes with an increase in the operational temperature, which is usually maintained at 40–45∘C in industrial-scale reactors. Keywords: biomining, bioleaching, acidophilic microorganisms, sulfide minerals, pyrite